2013
DOI: 10.1111/codi.12036
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options to improve anorectal function following rectal resection: a systematic review

Abstract: Conservative therapies such as pelvic floor re-education and colonic irrigation can improve anorectal function. SNS might be an effective solution in selected patients. However, methodologically qualitative studies are limited and randomized controlled trials are needed to draw evidence-based conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 55 publications
(206 reference statements)
5
33
0
3
Order By: Relevance
“…Although the review reported beneficial effects of conservative therapies on anorectal function after rectal resection, the papers reviewed were of limited methodological quality with heterogeneous patient populations, such as patients with rectal cancer, cervical cancer, and undefined pathology. 20 The findings of this systematic review on specific bowel cancer populations are consistent with the 5 th International Consultation on Incontinence, which recommends PFMT as an early intervention in the treatment of fecal incontinence in general adult populations. 17 The results of the present study demonstrate a modest reduction in stool frequency and incontinence episodes measured by patient bowel diary or patient report after PFMT.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Although the review reported beneficial effects of conservative therapies on anorectal function after rectal resection, the papers reviewed were of limited methodological quality with heterogeneous patient populations, such as patients with rectal cancer, cervical cancer, and undefined pathology. 20 The findings of this systematic review on specific bowel cancer populations are consistent with the 5 th International Consultation on Incontinence, which recommends PFMT as an early intervention in the treatment of fecal incontinence in general adult populations. 17 The results of the present study demonstrate a modest reduction in stool frequency and incontinence episodes measured by patient bowel diary or patient report after PFMT.…”
Section: Discussionsupporting
confidence: 79%
“…The findings in this review are in line with a previous systematic review on treatment options for improving anorectal function after rectal surgery for patients with or without cancer . The previous review examined fifteen studies, which included heterogeneous treatment options, such as pelvic floor re‐education (seven out of fifteen studies), colonic irrigation, and sacral nerve stimulation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Therefore, these side effects of treatment are frequently missed or overlooked 13. Encouragingly, recent studies suggest that incremental improvements in bowel dysfunction can be achieved14 and the results of the optimising radiotherapy bowel injury therapy (ORBIT) study demonstrate that a detailed clinical algorithm of targeted treatment strategies can improve radiotherapy-induced symptoms 15…”
Section: Introductionmentioning
confidence: 99%